P-006 The use of iv tpa beyond 6 hours from last known normal: data from the real world. (23rd July 2017) - Hedayat, H; Binning, M; Veznedaroglu, E; Budzik, R; English, J; Baxter, B; Bartolini, B; Liebeskind, D; Krajina, A; Gupta, R; Nogueira, R
Abstract : Objective: Intravenous tissue plasminogen activator (IV tPA) is the standard medication used for chemical thrombolysis in acute ischemic stroke when used within 4.5 hours from time of last known normal. Recent randomized trials demonstrate superiority of mechanical thrombectomy when combined with IV tPA versus IV tPA alone. Real world outcomes of patients who receive IV tPA beyond 4.5 hours from last known normal have not been well studied in large patient cohorts undergoing mechanical thrombectomy. The Trevo Registry is designed to assess real world outcomes of the Trevo Retriever in patients experiencing acute ischemic stroke. This is the largest prospective study for acute stroke intervention that has currently enrolled 1267 patients with 90 day outcomes data. Outcomes of patients who received IV tPA after 4.5 hours of symptom onset combined with mechanical thrombectomy were studied. Methods: The study design is a prospective, open-label, consecutive enrollment, multi-center, international registry of all patients who undergo mechanical thrombectomy for acute stroke using the Trevo stent retriever as the initial device. Enrollment is expected to reach 2000 subjects at up to 100 sites. Subgroup analysis of enrolled patients who received IV tPA beyond 4.5 hours of symptom onset and with 90 day follow-up was performed. Results: As of July 2016, a total of 994 patients were enrolled. The median NIHSS at admission was 15.5 (IQR 11–20). 478 patients (48.7%) received IV tPA within the 4.5 hour window or less from last known normal with a median procedure time of 50 min (8–286 min). In the 5% of patients treated who received IV tPA beyond 4.5 hours from time last known well, the revascularization rate was 90.5% and the rate of intracranial hemorrhage 2.1% and 90 day mRS ≤2 was 37.4%. The symptomatic intracerebral hemorrhage rate was 1.8% using ECASS III criteria. Subgroup analysis of patients who received IV tPA within 4.5 hours of symptom onset and those receiving it beyond 4.5 hours showed no significant difference in patient demographics or medical comorbidities. In addition, there was no difference in complication rate or 90 day outcome between the two groups. Conclusions: The Trevo Retriever Registry represents the first look at real world data with stent retriever use in the era of clinical trials showing the overwhelming benefit of stent retrievers to treat large vessel occlusive acute stroke. This data represents real world use of the Trevo Retriever including those who received IV tPA beyond 4.5 hours from initial stroke symptoms and adds to the data from recent trials with restricted eligibility criteria. Disclosures: H. Hedayat: None. M. Binning: None. E. Veznedaroglu: None. R. Budzik: None. J. English: None. B. Baxter: None. B. Bartolini: None. D. Liebeskind: None. A. Krajina: None. R. Gupta: None. R. Nogueira: None.